Respons Pertumbuhan dan Hasil Bawang Merah yang Ditanam pada Lahan Kering Ultisol terhadap Aplikasi Kompos Kiambang - Irianto Irianto; Budiyati Ichwan; Risti Gustriani (Jurnal Media Pertanian, 2022)
Shallots are vegetables that have high economic value. Shallots market demand in Indonesia increase over years in order to fulfil national consumption and exports. It is necessary to increase production by cultivating shallots in Utisol dry land which has low fertility and limited water availability. The fertilization with Salvinia molesta compost is an effort to increase the production and productivity of shallots in Ultisol dry land. This study aims were to investigated the effect of Salvinia molesta compost on the growth and yield of shallots, and to obtain the highest yield of Salvinia molesta compost. The study used a randomized block design (RAK) with one factor, the dose of Salvinia molesta compost were 0 ; 5; 10 ; 15 ; 20 ; and 25 tons ha-1. Each treatment was repeated four times. Salvinia molesta compost has no effect on growth, but is able to increase the yield of shallots. The dose of Salvinia molesta compost of 25 tons ha-1 resulted in the highest shallot bulb weight of 589.07 g m-2 (equivalent to 5.89 tons ha-1) an increase of 253.77% compared to the dose of 0 tons ha-1 (without Salvinia molesta compost).  Addition of Salvinia molesta compost up to a dose of 25 tons ha-1 still continues to increase tuber yields per m2.Keywords: organic matter, shallots, production